A Theoretical Comparative Review of Computer-Aided Landscape Design Tools: Features, Benefits, and Limitations - Mandani, Sami Abdullah; Aljasem, Abdullah Ebrahim (Journal of engineering sciences and information technology, 2023)
This study presents a theoretical comparative review of computer-aided landscape design tools, focusing on their features, benefits, and limitations. The aim is to provide landscape professionals with a comprehensive understanding of different software options available for their design projects. The study explores popular tools such as SketchUp, AutoCAD Architecture, Chief Architect, Revit, and Home Designer Suite, analyzing their capabilities and suitability for landscape design. Additionally, classification criteria for assistance programs in landscape design, including price, two-dimensional design, printing, integration with other architectural programs, lighting, blooming sites, botanical library, plant growth simulation, and land topography, are discussed. The study concludes by offering valuable insights and recommendations for professionals to make informed decisions when selecting computer-aided landscape design tools.
Keywords: Computer aided; design; landscape design; Innovation